Swedish labor market training and the duration of unemployment - Katarina Richardson; Gerard J. van den Berg (Institute for the Study of Labor (IZA), 2006)
The vocational employment training program is the most ambitious and expensive training program in Sweden and a cornerstone of labor market policy. We analyze causal effects on the individual transition rate from unemployment to employment by exploiting variation in the timing of treatment and outcome, dealing with selectivity on unobservables. We demonstrate the appropriateness of this approach in our context by studying the assignment. We also develop a model allowing for duration dependence and unobserved heterogeneity (leading to spurious duration dependence) in the treatment effect, and we prove non-parametric identification. The data cover the population and include multiple unemployment spells for many individuals. The results indicate a large significantly positive effect on exit to work shortly after exiting the program. The effect at the individual level diminishes after some weeks. When taking account of the time spent in the program, the effect on the mean unemployment duration is often close to zero
Keywords: 330